EVALUASI PROGRAM PEMBELAJARAN TAHFIDZ QURAN DI MASA PEMBELAJARAN PANDEMI COVID-19 - Wahyu Nurrohman; Andi Prastowo (Jurnal PAI Raden Fatah, 2022)
The Covid-19 virus pandemic that has shaken the world has affected all aspects of life, whether political, economic, social, and educational. During this Pandemic, many schools were forced to close and forced to go online. In the new order era, several pesantren were opened and learning was conducted offline (outside the network). One of them is Pesantren Tahfiz Daarul Quran Takhasus II Cikarang. Pondok Pesantren Tahfiz Daarul Qur'an Takhasus II Cikarang is an Islamic boarding school whose focus of learning is memorizing the Qur'an. At the beginning of the pandemic, Islamic boarding schools adopted a policy of repatriating their students as an effort to prevent the spread of the virus and carry out online learning (on the network). The result of this study is that learning tahfiz during the pandemic, both offline and online, is carried out using the sorogan and sima'i techniques. The difference is when online, the allocation of study time is reduced to 2 meetings via WhatsApp Video Call. And when offline learning, tahfiz returns to 4-5 meetings with students using masks and health protocols. The conclusion of this study is that offline Tahfiz learning is more effective than online Tahfiz learning, this can be seen based on the quantity of memorization and student learning motivation which is better when learning Tahfiz face-to-face or offline.